Koncepcja ustroju państwa w dokumentach Vaticanum Secundum - Kamińska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Vaticanum Secundum distinguished a single form of political system: democracy. Yet the Church’s approval of democracy comprises its institutional realm only. The Vatican Council’s documents deny the liberal model of democracy, and Paul VI actually condemned ‘philosophical liberalism’ in his letter Octogesima adveniens, when he claimed that it was based on erroneous foundations. Formulating its attitude to democracy the Church adopted a method of ‘balancing out’. According to the doctrinal statements of Vaticanum Secundum and their analysis outlined above, the model which is best adjusted to the modern reality is a specific mixed system, which obviously needs to be based on Christian axiology.